2009
DOI: 10.1371/journal.pone.0004751
|View full text |Cite
|
Sign up to set email alerts
|

MMPs Regulate both Development and Immunity in the Tribolium Model Insect

Abstract: BackgroundMatrix metalloproteinases (MMPs) are evolutionarily conserved and multifunctional effector molecules in development and homeostasis. In spite of previous, intensive investigation in vitro and in cell culture, their pleiotrophic functions in vivo are still not well understood.Methodology/Principal FindingsWe show that the genetically amenable beetle Tribolium castaneum represents a feasible model organism to explore MMP functions in vivo. We silenced expression of three insect-type Tribolium MMP paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
76
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 60 publications
14
76
0
1
Order By: Relevance
“…For example, Drosophila Doc has a morphogenetic role in the wing imaginal disc, where it regulates extracellular matrix remodeling through Matrix metalloproteinase 2 (Mmp2, Sui et al, 2012). However, we found that parental RNAi against the Tribolium orthologue was lethal prior to the SW stage, in contrast to results from Knorr et al (2009) (Fig. S8).…”
Section: Mid-development Tc-docmentioning
confidence: 70%
“…For example, Drosophila Doc has a morphogenetic role in the wing imaginal disc, where it regulates extracellular matrix remodeling through Matrix metalloproteinase 2 (Mmp2, Sui et al, 2012). However, we found that parental RNAi against the Tribolium orthologue was lethal prior to the SW stage, in contrast to results from Knorr et al (2009) (Fig. S8).…”
Section: Mid-development Tc-docmentioning
confidence: 70%
“…Moreover, the phenotype of AgTIMP silencing might also have implications for AgMMP2 (Fig. S3C) and AgMMP3 in parasite development, since it is an efficient inhibitor of all three metalloproteases of the mosquito, as supported by its homologues in Drosophila and Tribolium (7,56).…”
Section: Resultsmentioning
confidence: 99%
“…accumulates in large vesicles in the form of zymogen, which is also produced at high levels in Anopheles hemocyte-like Sua 4.0 cells and is constitutively secreted in the cell supernatant. Interestingly, the homologue of AgMMP1 in Tribolium is also shown to be expressed in hemocytes of the organism (7,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations